A review of electric vehicle technology: Architectures, battery technology and its management system, relevant standards, application of artificial intelligence, cyber security, and interoperability challenges - Vincent M. Macharia; Vijay K. Garg; Dinesh Kumar (IET Electrical Systems in Transportation)
Abstract Currently, there is an increased global climate change awareness, and the world is tending towards net zero emissions. The transportation sector is leading in Green House Gas emissions (GHG). Furthermore, the diminishing reserves of fossil fuels, the need for cheaper maintenance vehicles, more efficient drive trains, and better performance vehicles presents a challenge in ICE. Electric Vehicles (EVs) offer the perfect mobility solution which can replace the conventional ICE in the near future. This article comprehensively reviews the components and advances in the various technologies employed in electric vehicles to achieve efficiency in motion and optimise energy management in electric vehicles. This article gives an analysis of the current EV scenario globally. It then details the different configurations of electric vehicle architectures available. The battery is discussed, and the various electrochemical technologies are analysed. Battery Management Systems (BMS) to efficiently manage energy are discussed. The charging methods, voltage levels, and relevant standards are outlined in detail. The traction motors and power conversion technologies are reported with advancements in electric vehicle applications. Furthermore, this article gives a comprehensive overview of various emerging technologies, such as the Internet of Things (IoT), Artificial Intelligence (AI) & Machine Learning (ML), to improve EVs' performance through digitalisation. On the other hand, cybersecurity has become an ever‐challenging issue in EVs due to the increasing use of digital technologies. This article thoroughly overviews cybersecurity challenges in EV applications and explains possible proactive measures. Interoperability arising from various EV manufacturers' many different charging designs is discussed.